2015
DOI: 10.1016/j.yfrne.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor-acting neurosteroids: A role in the development and regulation of the stress response

Abstract: HighlightsGABAA receptors (GABAARs) curtail stress-induced activation of the HPA axis.Stressful challenges evoke de novo brain synthesis of GABAAR-active neurosteroids (NS).NS inhibit the output of CRF-releasing neurones of the hypothalamus.NS actions in the hypothalamus are blunted in rodent models of early-life adversity.NS may be important molecular messengers in the programming of the stress-response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 313 publications
2
104
0
Order By: Relevance
“…Numerous expression studies using recombinant receptors indicated that receptors composed of α, β, and γ subunits form GABAA receptors with a pharmacological profile that mimic properties of the majority of native receptors. Despite the fact that the immense number of different pentameric combinations can be assembled from the pool of native protein subunits, it seems that the prevalent form of native GABAA receptors is the combination of two α, two β and a single γ, δ or ε subunit [30,31]. As mentioned before, isoform α1β2γ2 is considered as the most prevalent subtype of adult GABAA receptors, with γ2β2α1β2α1 counter-clockwise arrangement surrounding central ion pore when viewed from the synaptic cleft [32].…”
Section: Subunit Composition Determines Pharmacological Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous expression studies using recombinant receptors indicated that receptors composed of α, β, and γ subunits form GABAA receptors with a pharmacological profile that mimic properties of the majority of native receptors. Despite the fact that the immense number of different pentameric combinations can be assembled from the pool of native protein subunits, it seems that the prevalent form of native GABAA receptors is the combination of two α, two β and a single γ, δ or ε subunit [30,31]. As mentioned before, isoform α1β2γ2 is considered as the most prevalent subtype of adult GABAA receptors, with γ2β2α1β2α1 counter-clockwise arrangement surrounding central ion pore when viewed from the synaptic cleft [32].…”
Section: Subunit Composition Determines Pharmacological Effectsmentioning
confidence: 99%
“…Drugs acting at benzodiazepine binding sites can only modulate GABAA receptors, while barbiturates, neuroactive steroids and anesthetics at higher concentrations are able to directly activate GABAA receptors in the absence of GABA [31,[59][60][61][62][63]. Binding sites for all of these drugs are allosterically coupled.…”
Section: Modulation Of Gabaa Receptors By Pharmacological Agentsmentioning
confidence: 99%
See 3 more Smart Citations